Evaluation of the thermoplasticity of different gutta-percha cones and the TC system - Tanomaru-Filho, Mário [UNESP]; Bier, Carlos Alexandre Souza [UNESP]; Tanomaru, Juliane Maria Guerreiro [UNESP]; Barros, Danilo Barbosa [UNESP] (FapUNIFESP (SciELO), 2007)
Objective: The aim of this study was to evaluate the thermoplasticity of three commercial brands of gutta-percha (Tanari, Dentsply 0.06, and Roeko), and of the TC system. Materials and Methods: Standardized specimens were fabricated from the materials to be evaluated. Specimens were placed in water at 70°C for 60 seconds. Following that, they were positioned between two glass slabs and each set was compressed by a 5kg weight. Images of the specimens before and after compression were digitized and analyzed by the Image Tool software. The flow capacity of each material was confirmed by the difference between the initial and final areas of each sample. Results: The resulting data were analyzed by ANOVA. The TC system presented the greatest thermoplasticity values (p<0.05). Among the gutta-percha cones, the Roeko brand showed higher thermoplasticity than the others (p<0.05). Conclusion: The gutta-percha from TC system present good thermoplasticity capacity.
Keywords: Endodontics; Gutta-percha; Root canal obturation